PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Riswan Ludfi; Iqbal Firdaus (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
The aims of this research were to know : (1) The influence of CSR variables (employee, environment, community) as independent varables either partially or simultaneously towards Return on Assets (2) The influence of CSR variables(employee, environment, community) as independent varables either partially or simultaneously towards Tobin’s Q. The method of this research is multiple linear regression analysis. The research sample were taken from Corporate’s data on IDX through annual report and financial information from financial reports for manufacturers, developers, and miners (just typically pure trading corporates were not included) in the period 2010 to 2012 with the purposive sampling method. There were 95 of the companies that met the criteria and were accumulated for three years, so total of samples became 285 samples. The result of research showed that all of CSR variables gave positive significant influence simultaneously towards the dependent variables of ROA and Tobin’s Q. Partially, the variables of employees and community were positively significant influencing the dependent variable of ROA, and only employees as the independent variable had positive influence towards Tobin’s Q